ISSUES OF IMPROVING THE COMPLIANCE CONTROL SYSTEM IN THE FIGHT AGAINST THE SECRET ECONOMY AND CORRUPTION (Proceedings of International Educators Conference, 2024)
This article is a systematic explanation of its main content, causes and types of occurrence and consequences, types of struggle against the hidden economy and analyzes of its effective ways as one of the main problems that are growing in the economic sphere of the countries of the world.